2022
DOI: 10.3390/ijms23052803
|View full text |Cite
|
Sign up to set email alerts
|

Free Cholesterol Accelerates Aβ Self-Assembly on Membranes at Physiological Concentration

Abstract: The effects of membranes on the early-stage aggregation of amyloid β (Aβ) have come to light as potential mechanisms by which neurotoxic species are formed in Alzheimer’s disease. We have shown that direct Aβ-membrane interactions dramatically enhance the Aβ aggregation, allowing for oligomer assembly at physiologically low concentrations of the monomer. Membrane composition is also a crucial factor in this process. Our results showed that apart from phospholipids composition, cholesterol in membranes signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Particularly important appears to be the role of hydrophobic interaction of amyloid-prone proteins/peptides with membranes and/or with the individual membrane components (Jelinek and Sheynis, 2010;Nault et al, 2013). It is currently accepted, that membrane composition is the factor controlling the aggregation process (Necula et al, 2003;Gorbenko and Kinnunen, 2006;Bucciantini et al, 2014;Banerjee et al, 2021;Hashemi et al, 2022). Lipid bilayers may act as conformational catalysts, favoring protein misfolding and inducing the growth of aggregation nuclei, early oligomers, and mature fibrils with specific biophysical, structural, and toxicity features (Bucciantini et al, 2014;Korshavn et al, 2017;Rangachari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Particularly important appears to be the role of hydrophobic interaction of amyloid-prone proteins/peptides with membranes and/or with the individual membrane components (Jelinek and Sheynis, 2010;Nault et al, 2013). It is currently accepted, that membrane composition is the factor controlling the aggregation process (Necula et al, 2003;Gorbenko and Kinnunen, 2006;Bucciantini et al, 2014;Banerjee et al, 2021;Hashemi et al, 2022). Lipid bilayers may act as conformational catalysts, favoring protein misfolding and inducing the growth of aggregation nuclei, early oligomers, and mature fibrils with specific biophysical, structural, and toxicity features (Bucciantini et al, 2014;Korshavn et al, 2017;Rangachari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A significant effect of lipid bilayers has been investigated in detail for Aβ peptide aggregation (Matsuzaki, 2007;Lin et al, 2009;Korshavn et al, 2017;Iadanza et al, 2018;Hashemi et al, 2022;Mrdenovic et al, 2022). The strongest evidence causally linking cholesterol to AD is provided by experimental studies showing that adding or reducing cholesterol alters amyloid precursor protein (APP) and Aβ peptide levels (McLaurin et al, 2003;Wood et al, 2003;Lin et al, 2009;Banerjee et al, 2021;Hashemi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cholesterol also contributes to membrane fluidity, promoting the packing of lipids, and is suggested to have a high affinity for Aβ, particularly by the fraction Aβ25–35 that could penetrate in the cholesterol monolayer [ 44 , 45 , 57 ]. Also, cholesterol participates in the amyloid pore’s formation, induced by different Aβ peptides (Aβ1–42, Aβ22–35, and Aβ25–35) [ 58 , 59 , 60 ]. In addition, multiple evidence has indicated that the amyloidogenic processing of AβPP occurs in specialized domains of the membrane known as lipid rafts [ 61 , 62 ].…”
Section: Aβ/app-cellular Membrane and Lipid Influencementioning
confidence: 99%